Decoding the mannose receptor-mAb interaction: the importance of high-mannose N-glycans and glycan-pairing - Julia Baumeister; Maximilian Meudt; Sybille Ebert; Frank Rosenau; Boris Mizaikoff; Michaela Blech; Kristina M. J. Aertker; Fabian Higel (mAbs)
During the development process of therapeutic monoclonal antibodies (mAbs), it is crucial to control (critical) quality attributes such as N-glycosylation influencing pharmacokinetics (PK) and Fc effector functions. Previous reports have shown that mAbs containing high-mannose N-glycans are cleared faster from blood circulation, leading to reduced half-lives. The high-mannose N-glycan content of mAbs can be influenced during the cell culture process by factors such as cell lines, process conditions, and media. Furthermore, mAbs have either one high mannose N-glycan (asymmetrical high-mannose glyco-pair) or two high mannose N-glycans (symmetrical high-mannose glyco-pair). The hypothesis that the mannose receptor (MR, CD206) accelerates clearance by facilitating their internalization and subsequent lysosomal degradation is widespread. However, the interaction between MR and mAbs has not been explicitly demonstrated. This study aimed to investigate this interaction, providing the first systematic demonstration of MR binding to the Fc region of mAbs with high-mannose N-glycans. Two novel analytical methods, MR surface plasmon resonance and MR affinity chromatography, were developed and applied to investigate the MR-mAb interaction. The interaction is found to be dependent on high-mannose content, but is independent of the mAb format or sequence. However, different glyco-pairs exhibited varying binding affinities to the MR, with the symmetrical high-mannose glyco-pair showing the strongest binding properties. These findings strengthen the hypothesis for the MR-mediated mAb interaction and contribute to a deeper understanding of the MR-mAb interaction, which could affect the criticality of high-mannose containing mAbs development strategies of IgG-based molecules and improve their PK profiles.